Qualitative Analysis of Real Drug Evidence Using DART-MS and the Inverted Library Search Algorithm - Sisco, Edward; Appley, Meghan G.; Tennyson, Stephen S.; Moorthy, Arun S. (Journal of the American Society for Mass Spectrometry, 2022)
Chromatographic-less mass spectrometry techniques like direct analysis in real-time mass spectrometry (DART-MS) are steadily being employed as seized drug screening tools. However, these newer analytical platforms require new computational methods to best make use of the collected data. The inverted library search algorithm (ILSA) is a recently developed method designed specifically for working with mass spectra of mixtures collected with DART-MS and has been implemented as a function in the NIST/NIJ DART-MS data interpretation tool (DIT). This paper demonstrates how DART-MS and the ILSA/DIT can be used to analyze seized drug evidence, while discussing insights gathered during the evaluation of 92 adjudicated case samples. The evaluation verified that the combination of DART-MS and the ILSA/DIT can be used as an informative tool to help analysts screen seized drug evidence but also revealed several factorssuch as the influence of incorporating multiple in-source fragmentation spectra and the effect of scoring thresholdsan analyst must consider while employing these methods. Use cases demonstrating the benefit of the nonscoring metrics provided by the ILSA/DIT and demonstrating how the ILSA/DIT can be used to identify novel substances are also presented. A summary of considerations for using the ILSA/DIT for drug screening concludes this paper.